2022
DOI: 10.1186/s40545-021-00403-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19 vaccines acceptance in the Lebanese population: a national cross-sectional study

Abstract: Background Vaccines have become the best weapon for epidemic prevention and control in the absence of standard approved effective therapies. However, skepticism about the vaccine efficacy and safety is constantly reported. To our knowledge, there has been no study assessing COVID-19 vaccine acceptance in Lebanon. The primary objective of this survey is to assess the COVID-19 vaccines’ acceptance and its related determinants in the Lebanese population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
6

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
2
12
6
Order By: Relevance
“… 16 Previous studies assessing acceptance towards vaccines revealed huge regional variability. The findings of our study were higher than that reported in a cross-sectional study conducted in Lebanon by Hanna et al, 17 which found that 63.4% of the Lebanese population accepted to receive the COVID-19 vaccine. Our findings were also higher than earlier studies conducted in the UK (71.7%), 18 the USA (69%), 19 Japan (65.7%), 20 and Saudi Arabia (64.7%), 21 but lower than the acceptance rate toward vaccination in China (88.6%).…”
Section: Discussioncontrasting
confidence: 90%
“… 16 Previous studies assessing acceptance towards vaccines revealed huge regional variability. The findings of our study were higher than that reported in a cross-sectional study conducted in Lebanon by Hanna et al, 17 which found that 63.4% of the Lebanese population accepted to receive the COVID-19 vaccine. Our findings were also higher than earlier studies conducted in the UK (71.7%), 18 the USA (69%), 19 Japan (65.7%), 20 and Saudi Arabia (64.7%), 21 but lower than the acceptance rate toward vaccination in China (88.6%).…”
Section: Discussioncontrasting
confidence: 90%
“…Almost 61.9% of the participants who had previously been infected with COVID-19 accepted the vaccine, while 20.3% refused. The acceptance rate in this the study was compatible with other results reported by different studies such as that in Lebanon (63.4%) [30] compared to a lower rate reported in Kuwait (53.1%) [10]. The results of this study are also compatible with similar studies conducted in the UK (64-71.7%) [16], t US (69%) [13], and Japan (65.7%) [14].…”
Section: Discussionsupporting
confidence: 91%
“…Some studies, such as our first phase study reported willingness to receive the vaccine using yes/no options, and may therefore overestimate the rate of vaccine acceptance due to incompatibility with the proposed structure of the SAGE Working Group on Vaccine Hesitancy (22). According to the results of cross-sectional studies based on the general population, in which only yes/no options were considered, the vaccine acceptance rate in Bangladesh was 79% (23), in Lebanon was 64% (24), in South Korea was 53% (25), and in Brazil was 81.4% (26); in our first phase vaccine acceptance was about 84% (14). Because the willingness to receive the vaccine is not a binary decision and a range of emotions and factors can be involved, in other studies, such as our study in Phase II, the response to the willingness to receive the vaccine was reported as "acceptance, " "definite unwillingness" and "not sure."…”
Section: Methodological Issuesmentioning
confidence: 99%